A CASE STUDY ABOUT A STUDENT’S RELUCTANCE TO SPEAK IN THE TARGET LANGUAGE IN CLASSROOM SETTING - Fernando, Sérgio Manuel Coelho; Lee, Adriana de Koning (Interfaces Científicas - Educação, 2018)
This small-scale case study attempts to explore the causes of one adult student’s reluctance to speak English in classroom in Aracaju, Brazil. The research employed semi-structured interviews and classroom observations to collect data. It will detail the reasons as to why the student is not at ease learning and speaking this foreign language and interpret the reasons why.